Pengaruh Personality dan Gender Terhadap Wawasan Lingkungan - Riwan Laraga (Publik : (Jurnal Ilmu Administrasi), 2017)
Personality is the human nature that dynamic to respond and react and interact relatively stable with other people or the environment in accordance with the underlying dimensions of personality that is conscientiousness, agreeableness, neuroticism, openness, extraversion in order to achieve personal goals. Gender is equity in the opportunity to actively participate in social programs based on gender differences factor. This means that the gender variable divide students according to gender. The purpose of this research is to know students perspective to the environmental insights related to personality and gender. This research use method ex post facto research with ANAVA 2x2 models. The instrument used in this study is a test. A view of students to the environment that are constructed in the human mind then reflected became the basis for interacting with the environment and action to the environment.. Male and female student have diversity of looking at the surrounding environment so that environmental insight of students who have a high personality better than the environment insight students have low personality Personaliti adalah sifat-sifat seseorang yg dinamis dalam merespon dan bereaksi serta berinteraksi yang relatif stabil dengan orang lain atau lingkungannya sesuai dengan dimensi yang mendasari kepribadian yaitu conscientiousness, agreeableness, neuroticism, openness, extraversion dalam rangka mencapai tujuan pribadi. Gender adalah kesetaraan dalam memperoleh kesempatan untuk berperan aktif dalam program sosial berdasarkan faktor perbedaan jenis kelamin. Hal ini berarti bahwa variabel gender membagi siswa menurut jenis kelamin. Penelitian ini bertujuan untuk mengetahui tetang cara pandang terhadap wawasan lingkungan yang berkaitan dengan personality dan gender. Penelitian ini menggunakan metode penelitian ex post facto dengan model ANAVA 2x2. Instrumen yang digunakan dalam penelitian ini adalah tes . Siswa pria maupun wanita memiliki keragaman dalam memandang lingkungan sekitarnya sehingga wawasan lingkungan siswa yang berpersonality tinggi lebih baik dari pada wawasan lingkungan berpersonality rendah dan wasawasan lingkungan pria lebih baik dari pada wanita.